Latitudinal diversity patterns of diatoms in the Southwestern Atlantic and Antarctic waters - Olguin Salinas, Hector; Alder, Viviana Andrea; Puig, Alba; Boltovskoy, Demetrio (Journal of Plankton Research)
Latitudinal changes in the species richness of planktonic diatoms in Southwestern Atlantic and Antarctic waters (29-76 S) were analyzed from local to regional scale in three spring and one summer seasons. A total of 220 diatom species (16-87 per station) were recorded. Despite the noticeable interannual variability, species richness showed a maximum in the northern sector of the Brazil-Malvinas Confluence Zone and a highly significant decrease with latitude. Fil: Olguin Salinas, Hector. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Ecología, Genética y Evolución de Buenos Aires. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Instituto de Ecología, Genética y Evolución de Buenos Aires; Argentina Fil: Alder, Viviana Andrea. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Ecología, Genética y Evolución de Buenos Aires. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Instituto de Ecología, Genética y Evolución de Buenos Aires; Argentina Fil: Puig, Alba. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Ecología, Genética y Evolución de Buenos Aires. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Instituto de Ecología, Genética y Evolución de Buenos Aires; Argentina Fil: Boltovskoy, Demetrio. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Ecología, Genética y Evolución de Buenos Aires. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Instituto de Ecología, Genética y Evolución de Buenos Aires; Argentina